2007
DOI: 10.1128/mcb.00104-07
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Autonomous Pi Regulation via Pit1 Plays a Role in Bone Mineralization

Abstract: The complex pathogenesis of mineralization defects seen in inherited and/or acquired hypophosphatemic disorders suggests that local inorganic phosphate (P i ) regulation by osteoblasts may be a rate-limiting step in physiological bone mineralization. To test whether an osteoblast autonomous phosphate regulatory system regulates mineralization, we manipulated well-established in vivo and in vitro models to study mineralization stages separately from cellular proliferation/differentiation stages of osteogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 46 publications
5
102
2
1
Order By: Relevance
“…Phosphate uptake by osteoblasts occurs concomitant with mineralization [30]. Studies by Yoshiko et al demonstrated that phosphate uptake via type III sodium-dependent phosphate cotransporter Pit-1, but not Pit-2, plays a crucial role in the regulation of bone mineralization both in vivo and in vitro [31]. Many osteotropic factors regulate phosphate uptake are associated with osteogenic differentiation and mineralization in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate uptake by osteoblasts occurs concomitant with mineralization [30]. Studies by Yoshiko et al demonstrated that phosphate uptake via type III sodium-dependent phosphate cotransporter Pit-1, but not Pit-2, plays a crucial role in the regulation of bone mineralization both in vivo and in vitro [31]. Many osteotropic factors regulate phosphate uptake are associated with osteogenic differentiation and mineralization in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrate a role for PiT1 in osteoblast-and chondrocyte-mediated mineralization (95)(96)(97). PiT1 expressed on matrix vesicles derived from the parent cell provides phosphate needed for mineralization.…”
Section: Pit1mentioning
confidence: 99%
“…However, it has been reported that Pit-1, one of the type-III sodium-dependent phosphate cotransporters, is necessary for increasing Pi uptake and consequently the Pi-induced expression of osteocalcin, osteopontin and other bone-related proteins during calcification in osteoblasts and vascular smooth muscle cells (Li and Giachelli, 2007;Yoshiko et al, 2007). It has been reported that BMP-2 promotes Pit-1 expression, Pi uptake and calcification in vascular smooth muscle cells, suggesting that vascular calcification shares a common mechanism with physiological calcification (Li et al, 2008).…”
Section: Pi-induced Osteogenesis and Inhibited Myogenesis In Skeletalmentioning
confidence: 99%